'Telephone interpreting should be used only as a last resort.' Interpreters' perceptions of the suitability, remuneration and quality of telephone interpreting. (2nd January 2018) - Wang, Jihong
ABSTRACT: This article reports on selected findings from a survey of 465 telephone interpreters in Australia, focusing on their opinions about the suitability, remuneration and quality of telephone interpreting. Results of this study revealed serious problems, such as telephone interpreting being used in inappropriate situations, and interpreters' dissatisfaction with the low remuneration for telephone interpreting. The majority of interpreters preferred on-site interpreting to telephone interpreting. However, interpreters' views on the accuracy of telephone interpretation versus on-site interpretation varied considerably. The key finding is that interpreters proposed various measures that would enhance the quality of telephone interpreting, indicating that interpreters, clients and interpreter employers need to work together to achieve that goal. These findings have implications for developing national protocols for telephone interpreting.